2017
DOI: 10.1111/pin.12508
|View full text |Cite
|
Sign up to set email alerts
|

High expression of Wls is associated with lymph node metastasis and advanced TNM stage in gastric carcinomas

Abstract: The roles of Wnt protein in carcinogenesis have been well documented in human cancers. Wls is a key modulator for the secretion of Wnt protein. We previously found that Wls was aberrantly expressed in colorectal carcinomas. Studies have revealed that dysregulation of Wnt signal transduction plays an important role in gastric carcinoma. We hypothesized that Wls may play a role in the development and progression of gastric carcinoma. In this study, three gastric cancer cell lines MGC-803, SGC-7901, and AGS, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…This can be used as a new landmark for the prognosis of gastric cancer. 42 The effects of these 10 key genes on EC have not been found, but our analysis shows that it plays B, Enrichment analysis of KEGG pathway as module gene. The color of the bubble represents the significance and the size represents the number of genes involved in the entry.…”
Section: Meg3mentioning
confidence: 74%
“…This can be used as a new landmark for the prognosis of gastric cancer. 42 The effects of these 10 key genes on EC have not been found, but our analysis shows that it plays B, Enrichment analysis of KEGG pathway as module gene. The color of the bubble represents the significance and the size represents the number of genes involved in the entry.…”
Section: Meg3mentioning
confidence: 74%
“…Wls protein was expressed in most of the ICC tissues tested (81.8%, score 2+ and 3+). Wls has been reported to be involved in the development of certain human cancers (Maruyama et al 2013;Lu et al 2015;Stewart et al 2015;Zhang et al 2017). Wls is overexpressed in malignant astrocytomas and promotes downstream Wnt signaling (Augustin et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Their data indicated that high CXCR4 expression is associated with ICC progression and metastasis via the canonical Wnt pathway. In previous studies, we investigated Wls expression and its clinical significance in gastric cancer and colorectal cancer and showed that Wls protein was differentially expressed in gastric cancer cell lines and tissue samples (Zhang et al 2017). High expression of Wls in gastric cancer was positively associated with well-differentiated tumor, lymph node metastasis, and advanced TNM stage.…”
Section: Introductionmentioning
confidence: 99%
“…Dysregulation of WNT processing can trigger UPR in cancer cells and by participating in WNT secretion, GPR177 mitigates ER stress. Aside from important roles in tissue development, GPR177 has been implicated in tumor initiation in several cancers . Although exact mechanisms of GPR177 action in cancer progression require further research, overexpression of GPR177 was previously shown to be positively correlated with cancer development .…”
Section: Discussionmentioning
confidence: 99%